Perancangan Alat Pemotong Kabel Otomatis Berbasis Programmable Logic Controller dengan HMI NB7W-TW00B - Rahmi Berlianti; Nasrul (Politeknik Manufaktur Negeri Bangka Belitung, 2020)
The use of human labor in measuring and cutting cables manually requires a long time plus the number of cables measured and cut in large quantities, it can take time and manpower so that the work is ineffective and cause losses. For this reason, this research was made a tool that can measure and cut cables automatically using the Programmable Logic Controller (PLC) Omron CP1E as its control system. In this automatic cable cutting tool the monitoring and input system uses HMI NB7W-TW00B. With this tool, it can measure cable lengths and directly cut them automatically so that it can save time and human labor in measuring and cutting the cable.